Site-selective probing of surfactant assemblies using excited state proton transfer of pyranine - Phukon, Aparajita (My University, 2018)
The thesis includes our investigations on the nature and behavior of water entrapped in the nano-confined surfactant assemblies, in particular, reverse micelles and micelles. The hydration behavior depends critically on the type of polar headgroup of surfactants and also on the presence of co-surfactants. We mainly employed the hydration sensitive excited state proton transfer (ESPT) property of a site selective anionic probe 8-hydroxypyrene-1, 3, 6-trisulfonate (HPTS or pyranine) to study these systems. In chapter 1, we briefly discuss the recent trends of various ESPT studies in different confined media and summarize how these dynamics differ from that in bulk water. Chapter 2 includes the summary of measurement techniques and experimental methods that we adopted in our studies. In the chapter 3, we investigated the effect of confinement on the solubility behaviour of the water pool of water/AOT/n-heptane reverse micelle towards a so called insoluble alcohol n-octanol. In Chapter 4, we confirmed the presence of finite level of hydration at the interface of a cationic surfactant reverse micelle (water/ BHDC/ benzene) by detecting non-negligible ESPT. The effect of co-surfactant on the hydration at the interfacial region of a quaternary water/CTAB/octanol/cyclohexane reverse micelle is discussed in the chapter 5. The modification of the interfacial hydration associated with the structural transition of water/DDAB/cyclohexane reverse micelle from rod to sphere is discussed in the chapter 6. In the chapter 7, we compared the interfacial properties between micelles formed by two different surfactants- zwitterionic sulfobetaine (SB12 and SB16) and cationic n-alkyl tertiary ammonium (DTAB and CTAB).
Sahu, Kalyanasis
Keywords: CHEMISTRY